AI, IoT, and blockchain breakthroughs in e-governance - Saini, Kavita 1976-; Gowri Ganesh, N. S. 1971-; Mummoorthy, A. 1983-; Chandrika, Roopa 1976- (IGI Global, 2023)
"The goal of this book is to clearly define and emphasize various AI algorithms, as well as new IoT and blockchain breakthroughs in the field of e-governance. The discipline of data analytics, security is on the verge of reaching new heights, thanks to the introduction of AI capabilities. Every chapter will cover blockchain technology, ML and DL algorithms, their origins, problems and benefits and various government use cases, to clearly explain the growing power of AI and security algorithms for the development and operation of e-governance applications. A thorough in-depth understanding of AI algorithms through real use case application can help to kindle interest in research. Students, scholars, bureaucrats, industrialists in and scientists interested in AI , cybersecurity and blockchain can greatly benefit from this book."
"Premier reference source"-- Cover
Kavita Saini, N.S. Gowri Ganesh, A. Mummoorthy und Roopa Chandrika sind die Herausgebenden
Keywords: Electronic government information -- Security measures; Public administration -- Data processing; Computer security; Blockchains (Databases); Internet of things; Artificial intelligence; Internet der Dinge; Künstliche Intelligenz; Computersicherheit; Blockchain; E-Government; Maschinelles Lernen